The Implementation of “Touch Massage” As A Non-Pharmacological Pain Management for Hepatocellular Carcinoma (HCC) Patients: Implementasi “Touch Massage” Sebagai Manajemen Nyeri Non Farmakologi pada Pasien Hepatocellular Carcinoma (HCC) - Asnah Sitohang, Nur; Br Sitorus, Hotnida (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Liver cancer or Hepatocellular Carcinoma (HCC) is one of the leading causes of death in the world. Right upper quadrant abdominal pain is the most commonly reported as a symptom. This can be caused by structural and functional changes in the peripheral and central nervous system that cause increased pain perception in patients and can affect the patient's quality of life. One of the treatments that nurses can provide is the provision of non-pharmacological therapy. The purpose of this case study is to provide nursing care for pain management in HCC patients through the nursing process. Participants in this case study were only one person diagnosed with HCC. The instrument used to measure pain scale is Visual Analogue Scale (VAS). The intervention provided is a soft and smooth massage given as long as pain appears in the leg and back area, carried out for 10-30 minutes when pain appears which is given for 4 days. The results of the evaluation showed that there was a decrease in the pain scale, namely before the VAS intervention 7-8 and after the VAS intervention to 4-6. This shows that the Touch massage technique can reduce pain levels in HCC patients.